Emphysematous cholecystitis in a young male without predisposing factors: A case report - Chen, Ming-Yu (Medicine (Baltimore), 2016)
This report describes the diagnosis and treatment for Emphysematous cholecystitis (EC) without predisposing factors, and reviews the current literature. A 49-year-old male without predisposition presented to emergency department with a two-day history of sudden onset abdominal pain, hypertension and received empirical antibiotics with Imipenem/Cilastatin 0.5 g via intravenous route every 8 hours. Computed tomography (CT)-scan revealed that air encircling gallbladder is the most important and accurate evidence for EC diagnosis. Laparoscopic cholecystectomy was performed, and no stone was seen in gallbladder. The patient's temperature and pulses returned to normal following laparoscopic cholecystectomy. The festering bile culture report showed E.coli and pathological analysis of the resected gallbladder disclosed that necrosis and mild mucosal dysphasia. The patient fully recovered without complication at outpatient clinic visit three months later. The EC is an acute infection of the gallbladder wall caused by gas-forming organisms, is a life-threatening cholecystitis with mortality rate as high as 25%. Therefore, the combination of laparoscopic cholecystectomy and antibiotics is recommended as soon as possible once the diagnosis of EC was a clean-cut.